Proximate Composition Analysis of Gracilaria sp. Seaweed from Local Coastal Waters - Nurwulan, Afrida; Bendi Sabela (SINTA Journal (Science, Technology, and Agricultural), 2025)
Gracilaria sp. is one of the commercially valuable seaweeds with potential applications in the food and industrial sectors, particularly due to its high polysaccharide content. This study aimed to determine the basic chemical composition of Gracilaria sp. through proximate analysis, including moisture, ash, protein, fat, and carbohydrate content. Samples were collected from Singkawang, West Kalimantan, and the results were compared with secondary data from various coastal regions in Indonesia. The proximate analysis showed that the Singkawang sample contained 79.80 ± 0.67% moisture, 1.29 ± 0.26% protein, 3.68 ± 0.07% fat, 0.89 ± 0.04% ash, and 14.38 ± 0.83% carbohydrates. Variation among regions indicates that environmental factors such as water substrate, sunlight exposure, nutrient availability, harvest age, and post-harvest treatment significantly influence the nutritional composition. Carbohydrates were identified as the dominant component, highlighting the potential of Gracilaria sp. as a source of dietary fiber and hydrocolloid material. Overall, the findings suggest that nutritional characteristics of Gracilaria sp. are strongly affected by geographical and handling factors, emphasizing the importance of standardized processing and proper cultivation site selection to optimize its utilization for food and industrial applications.